DIRECTORS AS DJ: AN ANALYSIS ON THE USAGE OF OLD SONGS AS A NARRATIVE TO AUGMENT THE EMOTIONAL DEPTH IN LOKESH CINEMATIC UNIVERSE - Saravanapperumal, Karuppiah; Ilampairthi, V. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Tamil film songs are always fresh and evergreen in the minds of the audience and always enjoy a separate fanbase. Famous Tamil film songs from previous films have been used in Tamil films for a quite long time; often in situations and scenes which are similar to the situations in which they had originally been sung. Interestingly, Lokesh Kanagaraj who is one of the well-known Tamil film directors in the Tamil film industry today, is very well known for re-using old Tamil film songs in his films which have become a recurring feature of his makings. However, unlike the other such instances, the old film songs have often been used in action scenes in his films which are totally unrelated to the contexts in which they had been written and sung originally. Thus, this style of re-using previous film songs in completely different contexts creates a new type of intertextuality for the audience and forces them to think about their association and nostalgia with these songs in a very different way and thus alters the personality of the sequence. This study will be analyzing this style of intertextuality in his films and also how Lokesh uses Tamil film songs in his films which constitute a part of the universe of the common characters in his film, Lokesh Cinematic Universe (LCU). It will also analyze the differences in the original contexts of such film songs in the films and the contexts of their placements in these respective films to understand how they have been used in the films. This study will adopt a methodology consisting of content analysis of the pre-existing songs in some selected films of Lokesh Kanagaraj along with their original video songs to understand and analyze their original context and situation and how they have been used in the films constituting a part of the Lokesh Cinematic Universe (LCU).